HOW ARTIFICIAL INTELLIGENCE HELPS PEOPLE IN EVERYDAY LIFE - Xalilova Zarnigor Muhammadjon qizi; Halimjonova Nozanin Abrorjon qizi (TADQIQOTLAR, 2025)
Abstract:  In  the  digital  era,  cybersecurity  has  become  a  fundamental requirement  for  protecting  information,  maintaining  privacy,  and  ensuring  the functionality  of  digital  systems.  As  individuals,  businesses,  and  governments increasingly rely on online platforms, cloud services, and connected devices, cyber threats  have  expanded  in  both  complexity  and  frequency.  These  threats  include malware attacks, phishing schemes, data breaches, identity theft, and disruptions to critical  infrastructure.  The  consequences  of  such  attacks  can  be  severe,  affecting financial stability, national security, social trust, and individual well-being. This paper explores the importance of cybersecurity, examines the most common types of cyber threats,  analyzes  the  societal  and  economic  implications  of  insecure  digital environments, and proposes practical strategies for enhancing digital safety. The study highlights the global need for cybersecurity awareness, stronger regulatory policies, and technological advancements to build a safe and resilient digital future.